TECHNOLOGY FOR DEVELOPING WRESTLERS' EXECUTION OF THE CHIL METHOD - Yorkinoy Ortiqova (Proximus Journal Publishing, 2024)
This article contains information on further improvement of the chil method using a set of general and special exercises to improve the chil method during wrestling training. In the given set of exercises, exercises on the development of technical and tactical movements and the physical qualities of the participants were mentioned. Recommendations on the development of the actions of the wrestlers during the competition have been implemented.
Keywords: special exercise; competition; movement; development